Barriers and facilitators affecting nurses’ ability to assess and prevent suicide in general hospitals in the Kingdom of Saudi Arabia: A cross-sectional study - Aljedaani, Shafeah; El-Bilsha, Mona (Belitung Raya Publisher - Belitung Raya Foundation, 2025)
Background: Suicide is a growing public health concern in Saudi Arabia, where rates have shown a gradual increase over recent decades. Nurses working in general hospital settings often encounter patients at risk but may face barriers that limit their ability to assess and prevent suicide effectively. Understanding these barriers and facilitators is essential to improve nurses’ preparedness and strengthening institutional suicide prevention efforts. Objective: This study aimed to explore the barriers and facilitators influencing nurses’ ability to assess and prevent suicide in general hospitals in the Kingdom of Saudi Arabia, and to identify factors associated with these perceptions. Methods: A quantitative, descriptive cross-sectional design was employed in three major government hospitals in Jeddah between April and May 2025. A structured self-administered questionnaire was developed based on the Capability, Opportunity, and Motivation–Behavior (COM-B) framework and validated through exploratory factor analysis using a randomly split dataset (200 cases for instrument validation and 347 cases for main analysis). The two-factor structure (barriers and facilitators) demonstrated strong construct validity (KMO = 0.962, Bartlett’s χ² = 9185.382, p <0.001) and explained 74.29% of the total variance. Data were analyzed using IBM SPSS version 26. Descriptive statistics summarized participant characteristics and perceptions, while independent-samples t-tests and multiple linear regression analyses examined predictors of perceived barriers and facilitators. Results: Among 347 nurses in the main analysis, the highest-rated barriers were limited time and heavy patient load (M = 3.81, SD = 0.96) and inadequate training (M = 3.72, SD = 0.99). The strongest facilitator was adequate training and continuing education (M = 3.80, SD = 1.05). Regression analyses showed that education level, total years of experience, and years in the current position significantly predicted perceived barriers (F = 12.16, p <0.001), explaining 9.6% of the variance (R² = 0.096), and of facilitators (F = 6.286, p <0.001), explaining 5.2% of the variance (R² = 0.052). Nurses without suicide-prevention training perceived more barriers (p = 0.004), whereas those with prior experience caring for suicidal patients reported greater awareness of both barriers and facilitators (p <0.05). Conclusion: Nurses’ capability, opportunity, and motivation to engage in suicide prevention appear to be influenced by workload pressures, limited training, and organizational factors. Strengthening structured education, implementing standardized assessment protocols, promoting interdisciplinary collaboration, and improving staffing support may enhance nurses’ preparedness and confidence in suicide risk assessment and prevention within general hospital settings.